(untitled) (Circe de clásicos y modernos, 2023)
This article analyzes the reception of Tacitus’ Germania as a reliable historical document in Nazi Germany, and the reading operations that the National Socialist regime carried out on the work with the aim of installing it as a source of its ideology. Thence, it will be shown how the primary function of Germania was subverted from fiction to history by means of cutting, biased translation, apocryphal quotation, and dissociation with its immediate context of production. This produced an interpretation of Germania as a mirror of the official ideology of racial conflict in Germany during the 1930s.